PENGGUNAAN KRIM EKSTRAK BATANG DAN DAUN SURUHAN (Peperomia pellucida L.H.B.K) DALAM PROSES PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH (Rattus norvegicus) - Nur Fitri (BIOPENDIX, 2015)
Background: Peperomia pellucida L'HBK or known as messengers in the Indonesian plant is a herbaceous plant that belongs to the family Piperaceae. This study aimed to determine the effect of the stem and leaf extract cream messengers to the healing process of burns in rats (Rattus norvegicus. Methods: This was an experimental study using a completely randomized design. Test animals were divided into three groups, each - each group consisted of 3 rats. The first group is the negative control group (distilled water), the second group is a positive control group (BioplacentonÂ®), the third group is the group treated stem and leaf extract cream errand. The diameter of the wound and fibroblasts observed histopathology and is used as an indicator of the healing process of burns. The burns were treated and observed the healing effect for 20 days. Data were analyzed statistically wound diameter using ANOVA followed by LSD test. Results: The results showed the cream extracts of stems and leaves telling effect on the healing process of burns on rats. Conclusion: The results also showed that the treatment group and the leaf stem extract cream messengers and control groups positively influence the healing process of burns significantly when compared to the negative control group. Meanwhile, the treatment group stem and leaf extract cream messengers have no preformance difference influence the healing process of burns a significant positive control group